2014
DOI: 10.1105/tpc.113.118687
|View full text |Cite
|
Sign up to set email alerts
|

A Wheat SIMILAR TO RCD-ONE Gene Enhances Seedling Growth and Abiotic Stress Resistance by Modulating Redox Homeostasis and Maintaining Genomic Integrity  

Abstract: Plant growth inhibition is a common response to salinity. Under saline conditions, Shanrong No. 3 (SR3), a bread wheat (Triticum aestivum) introgression line, performs better than its parent wheat variety Jinan 177 (JN177) with respect to both seedling growth and abiotic stress tolerance. Furthermore, the endogenous reactive oxygen species (ROS) was also elevated in SR3 relative to JN177. The SR3 allele of sro1, a gene encoding a poly(ADP ribose) polymerase (PARP) domain protein, was identified to be crucial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
153
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(159 citation statements)
references
References 79 publications
5
153
0
1
Order By: Relevance
“…3 (SR3) were reported as salinity tolerant lines due to their more tolerant of salinity than JN177 [4, 5], which were selected from the derivatives of an asymmetric somatic hybridization between the salinity sensitive line, bread wheat cultivar Jinan 177 (JN177) and the highly tolerant related species, tall wheatgrass ( Thinopyrum ponticum ) [4, 5]. Transcriptomic and proteomic experiments showed that imposing salinity stress induced the differential up- or down-regulation of many genes present in SR3, and some of these, when expressed as transgenes, produced a marked positive impact on the plant’s level of salinity tolerance [611]. Although field trials showed that SR3 out-performs SR4 in pH neutral saline soils, the reverse was the case in alkaline pH saline soils (unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…3 (SR3) were reported as salinity tolerant lines due to their more tolerant of salinity than JN177 [4, 5], which were selected from the derivatives of an asymmetric somatic hybridization between the salinity sensitive line, bread wheat cultivar Jinan 177 (JN177) and the highly tolerant related species, tall wheatgrass ( Thinopyrum ponticum ) [4, 5]. Transcriptomic and proteomic experiments showed that imposing salinity stress induced the differential up- or down-regulation of many genes present in SR3, and some of these, when expressed as transgenes, produced a marked positive impact on the plant’s level of salinity tolerance [611]. Although field trials showed that SR3 out-performs SR4 in pH neutral saline soils, the reverse was the case in alkaline pH saline soils (unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…The THI1 open reading frame (ORF) was amplified and cloned into either pBI221-GFP (Liu et al, 2014) or pAVA321-RFP. CPK33…”
Section: Subcellular Localization and Colocalizationmentioning
confidence: 99%
“…Interestingly, land plants possess a group of conserved and plant-specific PARP-like family proteins, with the PARP signature carrying the characteristic catalytic triad, H-Y-E, including Radical-induced Cell Death 1 (RCD1), Similar-to-RCD-One (SROs), and RCD-like proteins [16]. Although the Arabidopsis RCD1 was shown to be enzymatically inactive, the wheat SRO protein Ta-sro1 confers PARP activity in vivo and in vitro [17], suggesting the existence of additional and functional PARPs in plants. This may provide an explanation as to why the Arabidopsis atparp1parp2 mutant is phenotypically indistinguishable from the wild-type plants at the vegetative growth stage (Fig 1C), whereas the mouse parp1parp2 mutant is embryonically lethal.…”
Section: Adp-ribosylation: Similarities and Differences In Plants Andmentioning
confidence: 99%